Enzyme-assisted extraction for the recovery of bioactive chemicals from Vietnamese palm fruit peel - Thanh, Dao Van; Ha, Ho Thi Ngan; Tan, Nguyen Duy; Giang, Nguyen Thi Ngoc (Journal of Food Technology Research, 2025)
Palm fruit peel is regarded as agricultural waste and is inadequately exploited, even though it contains a high concentration of bioactive compounds. This work aimed to enhance the extraction process of vitamin C, total polyphenols, total flavonoids, total carotenoids, and extract recovery efficiency from the fruit peel of the palm (Borassus flabellifer L.) using an enzyme-assisted extraction method. The study was designed to optimize the critical parameters of the enzyme-assisted extraction process. The investigation involved two main stages: (i) assessing the influence of enzyme concentration (1-4%) and pH (4.0-5.5), and (ii) analyzing the impact of extraction duration (15-60 min) and temperature (40-55°C). This systematic approach was employed to find the ideal combination of conditions that would maximize the simultaneous recovery of all targeted compounds. The optimal conditions were determined to be a 2% enzyme concentration, a pH of 4.5, a temperature of 50°C, and an extraction duration of 45 minutes. Under these optimal parameters, the study successfully achieved an extraction yield exceeding 90%. Crucially, these conditions also succeeded in maximizing the recovery of all targeted bioactive compounds, including vitamin C, total polyphenols, total flavonoids, and total carotenoids. This work offers significant benefits by not only enhancing the potential value of palm peel by-products but also by providing a strong theoretical foundation for their industrial-scale application. The successful transformation of this agricultural waste into a valuable resource positions palm fruit peel as a promising raw material for high-demand sectors, including the functional food, cosmetic, and nutraceutical industries.